Determinants of adolescent pregnancy among primi gravida mothers attended for delivery in maternity hospital, Thapathali. - Chand, Mithu Devi (2002)
ABSTRACT: Adolescent pregnancy is associated with poor pregnancy outcome and poor maternal and child health. It is common problems in developing countries including Nepal. The reason for adolescent pregnancy must be identified to control the problem. To identify the contributing factors of adolescent pregnancy among primi gravida, a descriptive study was conducted in Indra RajyaLaxmi Devi maternity Hospital, Thapathali. Data collection was conducted during the period of 2058-06-+145, to 2058-07-14. A total of 100 prime non-adolescent postnatal mothers. Subjects were selected by non-probability convenient purposive sampling technique. Using semi-structured interview administered questionnaire collected information on social-demographic characteristics, reproductive history, contraceptive methods, personal behavior and recreational activities. In addition to interview, two focus groups discussion were conducted among the sub-group of study population. Data entering, processing and analysis was done by statistical computer software SPSS. To describe the data, frequency, percentage and mean was calculated and chi-square test was performed to analyze the association between dependent and independent variables. The finding revealed that the mean age of adolescent mother was 18.5 and 22.1 for non-adolescent mother. Seventy one percent of adolescent and 82% non-adolescent mothers were from rural area. Majority of them were from nuclear family (69% vs. 51%), literate (59% vs. 66%), housewife (95% vs. 89%), and were from income below Rs. 4000/month (50% vs. 45%). Regarding the type of marriage, love marriage was 58% vs. 41%, majority of them never practice contraceptive method in both groups (93% vs. 90%). The reason mentioned for early pregnancy in both groups was lack of knowledge on contraceptive method (89% vs. 94%) and many of them stated that providing contraceptive knowledge might prevent early pregnancy. Un-planned pregnancy was higher among adolescent group (56% vs. 7%). The finding from focus group was similar to interviewed findings such as the reason for early marriage and early pregnancy were, lack of knowledge on contraceptive method, family force, lack of decision making power and ignorance. In conclusion, to prevent adolescent pregnancy, general education should be emphasized, health education on contraceptive method, sex education, adolescent pregnancy and its impact on health of individual, family, and society should be provide. To change the socio-cultural norms and belief an interventional study with anthropological design may be needed.